Effects of Stromal Vascular Fraction and Platelet-Rich Plasma Treatment on Capillary Histopathology During Anal Trauma Healing in Rats: An in Vivo Study - -, Darwin; -, Sulmiati; -, Ahmadwirawan; Zainuddin, Andi Alfian; Josh , Fonny; Laidding, Sachraswaty Rachman; Mariana, Nita; Faruk, Muhammad (IIUM Medical Journal Malaysia, 2023)
INTRODUCTION: Anal traumas, such as blunt and penetrating injuries to the perineum, can disrupt the anal sphincter and cause considerable morbidity. Non-invasive anal trauma therapies have been widely developed, including growth factors administered as platelet-rich plasma (PRP) and stromal vascular fraction (SVFs) containing adipose[1]derived stem cells (ASCs) and limited growth factor. This study aimed to assess PRP and SVF effects on capillary histopathology in the anal trauma Wistar rat model. MATERIALS AND METHODS: This experimental study used a rat model. Rats were divided into three groups: Group A (n=12) was treated with PRP and SVFs; Group B (n=12) was treated with normal saline (placebo); Group C (n=4) was sacrificed on day 0 to obtain baseline capillary counts. Groups A and B were further divided into three subgroups, sacrificed on days 1, 7, and 14 post-treatment. RESULTS: Capillary counts significantly showed higher density between Groups A and B (p=0.037, analysis of variance). On day 7, there was a significant difference between Groups A and B (p=0.001). CONCLUSION: Mean capillary density significantly improved in anal trauma treated with a combination of PRP and SVFs compared to control. Our findings support the use of PRP and SVFs to aid recovery of patients with anal trauma.